Where's the Working Class? - Peter Goodwin (tripleC: Communication, Capitalism & Critique)
From the Communist Manifesto onwards, the self-emancipation of the working class was central to Marx’s thought. And so it was for subsequent generations of Marxists including the later Engels, the pre-WW1 Kautsky, Lenin, Luxemburg, Trotsky and Gramsci. But in much contemporary Marxist theory the active role of the working class seems at the least marginal and at the most completely written off. This article traces the perceived role of the working class in Marxist theory, from Marx and Engels, through the Second and Third Internationals, Stalinism and Maoism, through to the present day. It situates this in political developments changes in the nature of the working class over the last 200 years. It concludes by suggesting a number of questions about Marxism and the contemporary working class that anyone claiming to be a Marxist today needs to answer.